PENDIRIAN YAYASAN PASCA PUTUSAN MKRI : PENYELENGGARA PENDIDIKAN FORMAL OLEH SWASTA KEMBALI KE YAYASAN - Adjie, Habib (LPPM Unisba, 2010)
The law Number 9 Year 2009 concerning Educational Legal Entity which, among others, lost the binding force by the decision of the Constitutional Court of the Republic of Indonesia (MKRI), with the decision number 11-14-21-126-136 / PUU-VII/2009, dated March 31, 2010. The verdict has ended the implementation of formal education in the form of Educational Legal Entity. Therefore, a formal education held by the private entity shall be performed by a foundation. Nevertheless, there is a problem which has to be solved,Â Â namely the problem which is associated with the provisions of Article 39 of Government Regulation number 63 Year 2008. This paper tries to find solutions of formal education by private entity post-decision of Constitutional Court of Republic of Indonesia.